2004
DOI: 10.1074/jbc.m310179200
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-1/Tolloid-like Proteinases Process Dentin Matrix Protein-1

Abstract: Bone morphogenetic protein-1 (BMP-1)/Tolloid-like metalloproteinases play key roles in formation of mammalian extracellular matrix (ECM), through the biosynthetic conversion of precursor proteins into their mature functional forms. These proteinases probably play a further role in formation of bone through activation of transforming growth factor ␤-like BMPs. Dentin matrix protein-1 (DMP1), deposited into the ECM during assembly and involved in initiating mineralization of bones and teeth, is thought to underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(136 citation statements)
references
References 51 publications
(68 reference statements)
1
131
0
4
Order By: Relevance
“…Because of the objective of this study we have not identified the proteins or phosphorylation sites affected by a specific inhibitor. However, a comparison between the sizes of chick OPN (~60 kD), BSP (~70kD), and ON (~30kD) and the reported murine dentin matrix protein 1 (85-90 kD [48)) with the protein bands affected by phosphorylation inhibitors prompts us to speculate that phosphorylation of these proteins may have been reduced. This suggests that the inhibitors were functioning as predicted, and also that extracting with 2M guanidine hydrochloride enriched the extracts with these phosphorylated proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Because of the objective of this study we have not identified the proteins or phosphorylation sites affected by a specific inhibitor. However, a comparison between the sizes of chick OPN (~60 kD), BSP (~70kD), and ON (~30kD) and the reported murine dentin matrix protein 1 (85-90 kD [48)) with the protein bands affected by phosphorylation inhibitors prompts us to speculate that phosphorylation of these proteins may have been reduced. This suggests that the inhibitors were functioning as predicted, and also that extracting with 2M guanidine hydrochloride enriched the extracts with these phosphorylated proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Bone morphogenetic protein-1/tolloid-like proteinases, which are expressed in the bone and dentin as well as a variety of other tissues/cells [23], have been shown to cleave bacteria-derived recombinant DMP1 in vitro [24]. However, the in vitro cleavage pattern of DMP1 resulting from incubation with bone morphogenetic protein-1/tol-loid-like proteinases appeared different from that found in bone and dentin [12].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the COOH-terminal fragment of DMP1 in the nuclei suggests that it might be the COOH-terminal fragment rather than the full-length form that has transcriptional activity. It should be noted that the nuclear localization sequence is present at the COOH-terminal fragment of DMP1 [8].Bone morphogenetic protein-1/tolloid-like proteinases, which are expressed in the bone and dentin as well as a variety of other tissues/cells [23], have been shown to cleave bacteria-derived recombinant DMP1 in vitro [24]. However, the in vitro cleavage pattern of DMP1 resulting from incubation with bone morphogenetic protein-1/tol-loid-like proteinases appeared different from that found in bone and dentin [12].…”
mentioning
confidence: 99%
“…A recent study demonstrated that DMP1 is cleaved by bone morphogenetic protein-1, a metalloprotease important for extracellular matrix development (39). The knowledge that there is at least one and perhaps more than one enzyme linked to bone development important for DMP1 processing may explain the contradictory data relating to the cell culture effects of overexpression of DMP1, resulting in increased mineralization (13) and the time-dependent changes in the knockout in which, in most cases, excessive mineralization is seen, but in others (presumably those in which other PHEX and bone morphogenetic protein-1 substrates are in lower abundance), mineralization is deficient.…”
Section: Resultsmentioning
confidence: 99%